Why the Wait? Delayed HIV Diagnosis among Men Who Have Sex with Men - Nelson, Kimberly M. (Springer US, 2010)
We sought to identify factors associated with delayed diagnosis of human immunodeficiency virus (HIV; testing HIV-seropositive 6 months or more after HIV seroconversion), by comparing delayed testers to non-delayed testers (persons who were diagnosed within 6 months of HIV seroconversion), in King County, Washington among men who have sex with men (MSM). Participants were recruited from HIV testing sites in the Seattle area. Delayed testing status was determined by the Serologic Testing Algorithm for Recent HIV Seroconversion or a self-reported previous HIV-negative test. Quantitative data on sociodemographic characteristics, health history, and drug-use and sexual behaviors were collected via computer-assisted self-interviews. Qualitative semi-structured interviews regarding testing and risk behaviors were also conducted. Multivariate analysis was used to identify factors associated with delayed diagnosis. Content analysis was used to establish themes in the qualitative data. Out of the 77 HIV-seropositive MSM in this sample, 39 (51%) had evidence of delayed diagnosis. Factors associated with delayed testing included being African-American, homeless, “out” to 50% or less people about male-male sex, and having only one sex partner in the past 6 months. Delayed testers often cited HIV-related sickness as their reason for testing and fear and wanting to be in denial of their HIV status as reasons for not testing. Delayed testers frequently did not identify as part of the MSM community, did not recognize that they were at risk for HIV acquisition, and did not feel a responsibility to themselves or others to disclose their HIV status. This study illustrates the need to further explore circumstances around delayed diagnosis in MSM and develop outreach methods and prevention messages targeted specifically to this potentially highly marginalized population in order to detect HIV infections earlier, provide HIV care, and prevent new infections.